The national qualifications framework (NQF) - How will nursing education fit in? - Nelouise Geyer (AOSIS, 1997)
Authority Act no.58 of 1995, initiated a body that will develop such a framework. Opsomming Wet, No 58 van 1995, stel 'n liggaam daar omt so 'n raamwerk te ontwikkel. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.